Cross-Sectoral Collaborative Governance in School Health Services: A Multi-Case Study at Junior High Schools in North Minahasa Regency - Jilly Toar; Joulanda A.M. Rawis; Jeffry Sony Junus Lengkong; Beatrix J. Podung (JR Education, 2026)
This research aims to analyze the cross-sectoral collaboration patterns between the education and health sectors in managing School Health Services (UKS) and to develop a governance model adaptive to regional characteristics. The central problem is the phenomenon of Silo Mentality (sectoral ego) and the Health Coverage Gap, which hinders the effectiveness of school health services despite the region's Universal Health Coverage (UHC) status. Employing a qualitative multi-case study approach, this research was conducted at three types of junior high schools in North Minahasa Regency: Urban (SMPN 1 Airmadidi), Rural (SMPN 1 Dimembe), and Private (Manado Independent School). Data were collected through in-depth interviews, observations, and documentation, followed by cross-case analysis. The findings reveal that: (1) Collaboration patterns remain trapped in administrative formalities and are passive-reactive; (2) Bureaucratic barriers and the absence of resource pooling trigger systemic budgetary gaps in public schools; (3) This study successfully constructed an original model: The Mapalus Spiral Integrative-Adaptive (MSIA). The MSIA model transforms the local wisdom of Mapalus into a social technology that integrates digital presence and context-specific adaptive management. The implications of the study emphasize that effective UKS governance requires a shift from administrative leadership to adaptive leadership rooted in local collectivity and digital innovation.